Analisis Risiko Kesehatan Penggunaan Bahan Kimia di Unit Laboratorium Pendidikan Pontianak - Astaman Sultan; Lailatul Badriyah; Noeroel Widjajati (Media Gizi Kesmas, 2023)
Background: Laboratory Occupational Health and Safety (K3) quality must be continuously improved. Efforts that can be made are to carry out a risk assessment to determine the level of risk of using chemicals, to determine whether the risk is at an acceptable level or not and to determine risk control efforts. Effective control efforts will increase work productivity and reduce work accidents and work-related diseases. Objective: To study the level of health risks of using chemicals in Pontianak Education Laboratory Unit Method: The type of research used is qualitative research to assess the health risks of using chemicals. The study used modified AS/NZS 4360:2004 standards and the 2007 University of Arizona chemical risk assessment. The study was conducted within 1 month. Samples amounted to 24 materials. Data were analyzed descriptively by recording and identifying chemicals based on health consequences, then analyzing the risk of Results: chemicals based on standards and determining the level of chemical risk. 21 (87.5%) chemicals fall into the extreme risk category and the smallest risk from chemicals is in high risk level of 3 (12.5%) chemicals. Conclusion: The level of health risk of using chemicals is in the extreme risk category. It is necessary to carry out risk control in the form of providing K3 facilities according to standards, arranging chemicals, standardizing the ability / suction power of exhaust fans in fume hoods, installing ventilation, completing MSDS of chemicals, forming first aid and emergency response teams, providing training for laboratory assistants, providing food menus for detoxification, preparation of safety induction, and submission of reports on risk analysis results to policy makers for follow-up. Keywords: Health Risks, Chemicals, Laboratory